2014
DOI: 10.1155/2014/457350
|View full text |Cite
|
Sign up to set email alerts
|

A New Subspecies Identification and Population Study of the Asian Small-Clawed Otter (Aonyx cinereus) in Malay Peninsula and Southern Thailand Based on Fecal DNA Method

Abstract: Three species of otter can be found throughout Malay Peninsula: Aonyx cinereus, Lutra sumatrana, and Lutrogale perspicillata. In this study, we focused on the A. cinereus population that ranges from the southern and the east coast to the northern regions of Malay Peninsula up to southern Thailand to review the relationships between the populations based on the mitochondrial D-loop region. Forty-eight samples from six populations were recognized as Johor, Perak, Terengganu, Kelantan, Ranong, and Thale Noi. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Previous Malaysian mammal studies also conducted haplotype analyses of the mtDNA D-loop region using the DnaSP software. These haplotype analyses were conducted in the Asian elephant of Peninsular Malaysia (Elliza et al 2015) and in a population study of otters in Peninsular Malaysia in which a new subspecies of an otter was identified (Rosli et al 2014). Other loci, such as cytochrome b, have also been used, but these results are considered less effective.…”
Section: Haplotype Analysismentioning
confidence: 99%
“…Previous Malaysian mammal studies also conducted haplotype analyses of the mtDNA D-loop region using the DnaSP software. These haplotype analyses were conducted in the Asian elephant of Peninsular Malaysia (Elliza et al 2015) and in a population study of otters in Peninsular Malaysia in which a new subspecies of an otter was identified (Rosli et al 2014). Other loci, such as cytochrome b, have also been used, but these results are considered less effective.…”
Section: Haplotype Analysismentioning
confidence: 99%
“…This represents a limitation to a current suite of available species-specific primers (Holmes et al 2009); and the challenge is particularly great in samples of degraded DNA from processed products, such as dried or salted fins. The primers may not be 100% specific, or they may have annealed to the nuclear insertion of mtDNA (numts), which can compromise the identification process (Rosli et al 2014;Abdul-Latiff et al 2017). The DNA barcoding method using the universal primers targeting the COI loci were utilized in this analysis and provided with significantly good stretches of COI sequences of ~750 bp.…”
Section: Discussionmentioning
confidence: 99%
“…We used two methods of analysis in PAUP: first, neighbor joining with the Kimura 2-parameter model [7] to reconstruct a neighbor joining phylogram ( Fig. 3 ) and calculate the genetic distance ( Table 5 ), second, a maximum parsimony analysis with stepwise additions (1000 replicates) in a heuristic search [8] and 50% majority rule consensus ( Fig. 4 ).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%